2017
DOI: 10.1002/ajoc.201700223
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrollable Supramolecular Self‐Assembly of a Porphyrin Derivative that Contains a Polyhedral Oligomeric Silsesquioxane (POSS)

Abstract: In this study, we have synthesized a new photosensitive organic–inorganic POSS‐containing hybrid porphyrin derivative (H2TPP−Azo−POSS), in which azobenzene was used as a bridge to conjugate the porphyrin and POSS, by using click chemistry. The self‐assembly behavior of H2TPP−Azo−POSS was studied at different concentrations in CHCl3 and in CHCl3/n‐hexane mixed solvent systems. Our results showed that the self‐assembled morphology of H2TPP−Azo−POSS could be tuned by varying the concentration and polarity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Among the various types of external stimulus, light irradiation was regarded as an ideal candidate, because it was clean, facile, and no additives were required. [ 110 ] In general, the construction of photoactive system could be achieved by introduction of special photo‐sensitive chromophores. Recent advances of azobenzene‐based polymeric system has gradually become popular candidate due to the unique properties including photo‐induced phase transition, optical nonlinearities, photophysical birefringence and dichroism.…”
Section: Self‐assembly Of Poss‐based Hybrid Materials In Solutionsmentioning
confidence: 99%
“…Among the various types of external stimulus, light irradiation was regarded as an ideal candidate, because it was clean, facile, and no additives were required. [ 110 ] In general, the construction of photoactive system could be achieved by introduction of special photo‐sensitive chromophores. Recent advances of azobenzene‐based polymeric system has gradually become popular candidate due to the unique properties including photo‐induced phase transition, optical nonlinearities, photophysical birefringence and dichroism.…”
Section: Self‐assembly Of Poss‐based Hybrid Materials In Solutionsmentioning
confidence: 99%
“…The same research group, by following the LbL process and through a click approach, prepared other porphyrin-based molecular multilayer films (ITO-MP1-Zn) on indium tin oxide (ITO) electrodes for photovoltaic and photogalvanic devices [50]. Zhang and co-workers described the preparation of organic-inorganic hybrid porphyrin derivatives with a polyhedral oligomeric silsesquioxane (POSS) [51,52]. The authors followed two different synthetic approaches.…”
Section: Immobilization Of Porphyrins In Different Matrixesmentioning
confidence: 99%
“…The authors found that different morphologies, such as core-shell spherical micelles and ordered square sheets, can be obtained depending on the polarity of the solvent or solvent mixtures used [51]. The same group prepared the photosensitive organic-inorganic porphyrin-POSS hybrid P69 with an azobenzene bridge ( Figure 7) [52]. The synthetic route involved the reaction of porphyrin derivative P67 with 4-azido-4´-hydroxyazobenzene affording the formation of the porphyrin-azobenzene derivative linked by 1,2,3-triazole rings (50% yield).…”
Section: Immobilization Of Porphyrins In Different Matrixesmentioning
confidence: 99%
See 2 more Smart Citations